Neuroanatomical changes of ionotropic glutamatergic and GABAergic receptor densities in male mice modeling idiopathic and syndromic autism spectrum disorder - Nardi, Leonardo; Chhabra, Stuti; Leukel, Petra; Krueger-Burg, Dilja; Sommer, Clemens J.; Schmeisser, Michael J. (Frontiers in Psychiatry, 2023)
Autism spectrum disorder (ASD) comprises a wide range of neurodevelopment conditions primarily characterized by impaired social interaction and repetitive behavior, accompanied by a variable degree of neuropsychiatric characteristics. Synaptic dysfunction is undertaken as one of the key underlying mechanisms in understanding the pathophysiology of ASD. The excitatory/inhibitory (E/I) hypothesis is one of the most widely held theories for its pathogenesis. Shifts in E/I balance have been proven in several ASD models. In this study, we investigated three mouse lines recapitulating both idiopathic (the BTBR strain) and genetic (Fmr1 and Shank3 mutants) forms of ASD at late infancy and early adulthood. Using receptor autoradiography for ionotropic excitatory (AMPA and NMDA) and inhibitory (GABAA) receptors, we mapped the receptor binding densities in brain regions known to be associated with ASD such as prefrontal cortex, dorsal and ventral striatum, dorsal hippocampus, and cerebellum. The individual mouse lines investigated show specific alterations in excitatory ionotropic receptor density, which might be accounted as specific hallmark of each individual line. Across all the models investigated, we found an increased binding density to GABAA receptors at adulthood in the dorsal hippocampus. Interestingly, reduction in the GABAA receptor binding density was observed in the cerebellum. Altogether, our findings suggest that E/I disbalance individually affects several brain regions in ASD mouse models and that alterations in GABAergic transmission might be accounted as unifying factor.